THE USE OF ATEJI IN JAPANESE LIGHT NOVEL SEKAI SAIKOU NO ANSATSUSHA ISEKAI KIZOKU NI TENSEI SURU - Umam, Fajri Khoerul; Ali, Mohammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to describe the forms of ateji that appear in light novels based on the theory stated by Shirose (2012). The source of this research comes from Japanese light novel volumes 4-6 'Sekai Saikou No Ansatsusha, Isekai Kizoku Ni Tensei Suru'. This research used a descriptive qualitative method with a note-taking technique. The result is there are 25 ateji found in this novel which is if the same word of ateji appears, are eliminated and the result becomes 20 ateji. 5 classifications match and can be grouped into this classification. From these results, most of the distribution of ateji in the novel is in the classification of foreign languages, followed by the classification of ateji as pronoun, classification of ateji as an pronoun which complement each other, ateji that shows acronyms in foreign languages, and ateji special creation in this novel